Canine cutaneous mast cell tumors: A combined clinical and pathologic approach to diagnosis, prognosis, and treatment selection. (September 2016) - Sledge, Dodd G.; Webster, Joshua; Kiupel, Matti
Highlights: An evidence based approach to prognostication for canine cutaneous mast cell tumors can improve clinical decision making. Prognostic features including staging, grading, margin evaluation, and evaluation of molecular markers are reviewed. Algorithms for choosing local and systemic therapy are provided based on current understanding of prognostic features. Abstract: In view of the varied biologic behavior and the costs of treatment for canine cutaneous mast cell tumors, development of appropriate treatment plans for individual affected dogs can be difficult, but decisions regarding treatment should be made using a systematic, evidence-based approach. This manuscript reviews the current state of diagnostics and prognostication of canine cutaneous mast cell tumors, and suggests a combined approach based on clinical and pathologic assessment for decision making regarding treatment choices. The current state of histologic grading, evaluation of proliferation indices, evaluation of mutations in the c- kit gene and KIT expression, evaluation of excision and clinical staging are examined. On the basis of the current understanding of prognostication and treatment response, algorithms for selection of local and systemic therapy are presented.